Thyroid nodule rupture after thermal ablation for benign thyroid nodules: incidence, risk factors, and clinical management - Yu-tong Liu; Ying Wei; Zhen-Long Zhao; Jie Wu; Shi-Liang Cao; Na Yu; Yan Li; Li-Li Peng; Ming-an Yu (International Journal of Hyperthermia)
Background Thyroid nodule rupture (TNR) is a rare and severe complication after thermal ablation (TA), mostly from benign thyroid nodules (BTN).Objective To summarize the incidence of TNR after TA and analyze the causes and prevention strategies.Materials and methods This retrospective study enrolled 3971 patients who underwent TA for BTN from January 2014 to March 2024. The incidence, causes, and risk factors of TNR were analyzed. Propensity score matching (PSM) controlled for confounding factors. Multivariate regression identified risk factors for TNR. ROC curves determined the optimal cutoff value for the maximum diameter (MD) for TNR.Results TNR occurred in 8 cases [0.2% (8/3971)]. The mean time from TA to TNR was 29.6 ± 13.0 days (range, 20-60 days). After PSM, MD was larger in the TNR group than in the non-TNR group [mean 4.1 ± 1.6 cm vs. mean 1.8 ± 1.2 cm; p < 0.001]. The optimal cutoff value of MD for TNR was 2.75 cm. After PSM, the incidence of pressure on the ablation zone was significantly higher in the TNR group than in the non-TNR group [100% (8/8) vs. 0 (0/32); p < 0.001], which has been suspected as a case of TNR. Antibiotic drugs, aspiration, or incision drainage could successfully manage all TNR cases.Conclusion TNR could be encountered in case of pressure on the BTN after TA. Protecting the ablation site from pressure might be crucial in preventing TNR, especially within two months. TNR is more likely to occur if the MD of BTN exceeds 2.75 cm under pressure. Observation, antibiotics, and aspiration could successfully manage all TNR cases.